Shattered mirror - Johansen, Iris (New York : St. Martin's Press, 2018)
"Eve Duncan is thrown once more into a deadly game of intrigue. It begins when Eve receives a package containing a skull$1 (Band instructions for Eve to do her work reconstructing it. When she does, a beautiful woman$1 (Bs face emerges. But when Eve is introduced to the dead woman$1 (Bs mirror image, a game is on where her twin$1 (Bs life hangs in the balance."--s
Keywords: Duncan, Eve (Fictitious character) -- Fiction; Facial reconstruction (Anthropology) -- Fiction; Women sculptors -- Fiction; Thrillers (Fiction); Detective and mystery fiction